How nurses use National Early Warning Score and Individual Early Warning Score to support their patient risk assessment practice: A fieldwork study. (21st December 2022) - Langkjaer, Caroline S.; Bundgaard, Karin; Bunkenborg, Gitte; Nielsen, Pernille B.; Iversen, Kasper K.; Bestle, Morten H.; Bove, Dorthe G.
Abstract: Aim: To explore and describe how the National Early Warning Score (NEWS) and Individual Early Warning Score (I‐EWS) are used and how they support nurses' patient risk assessment practice. Design: A qualitative observational fieldwork study drawing on ethnographical principles was performed in six hospitals in two regions of Denmark in 2019. Methods: Data were generated from participant observations and informal interviews with 32 nurses across 15 different wards in the hospitals. A total of 180 h of participant observation was performed. The observations lasted between 1.5 and 8 h and were conducted during day or evening shifts. Results: NEWS and I‐EWS supported nurses' observations of patients, providing useful knowledge for planning patient care, and prompting critical thinking. However, the risk assessment task was sometimes delegated to less experienced staff members, such as nursing students and healthcare assistants. The Early Warning Score (EWS) systems were often adapted by nurses according to contextual aspects, such as the culture of the speciality in which the nurses worked and their levels of competency. In some situations, I‐EWS had the effect of enhancing nurse autonomy and responsibility for decision‐making in relation to patient care. Conclusions: EWS systems support nurses' patient risk assessment practice, providing useful information. I‐EWS makes it easier to factor the heterogeneity of patients and the clinical situation into the risk assessments. The delegation of risk assessment to other, less experienced staff members pose a risk to patient safety, which needs to be addressed in the ongoing debate regarding the shortage of nurses. Impact: The findings of this study can help ward nurses, hospital managers and policymakers to develop and improve strategies for improved person‐centred nursing care.